Leaders or villains? The role of corruption in shaping the stereotypes of politicians - Ascenso, I.; Ramos, M. R.; Moriconi, M.; Marques, S. (European Journal of Social Psychology, 2025)
The ways in which politicians are stereotyped contribute to perceptions of the legitimacy of their power, status and leadership. In this research, we examined how corruption impacts the stereotypes of politicians. By examining stereotype content, we posited that corruption should elicit morality-related traits, while in contexts of no corruption, both morality and competence should emerge as key dimensions. With two experiments (Ncombined = 272), participants were presented with either a corruption or no corruption condition and were asked to provide traits describing politicians. Results revealed that in the corruption conditions, (low) morality emerged as the key dimension explaining most variance. In the no-corruption conditions, (high) morality and (high) competence emerged as a single key dimension. Our findings reveal one of the multiple pathways by which corruption impacts society–perceiving politicians as having extremely low morality has implications for general trust and meritocracy, contributing to the erosion of democracy.